Workers' compensation : foundations for reform - Gunderson, Morley, 1945-; Hyatt, Doug (University of Toronto Press, 2000)
Topics covered include low back pain in workers' compensation, payroll taxes, unfunded liabilities, occupational health and safety, private participation, the cost, appeals litigation.
Keywords: Workers' compensation -- Canada.; Travail -- Accidents -- Indemnisation -- Canada.; POLITICAL SCIENCE -- Public Policy -- Social Security.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Workers' compensation; Canada